2021
DOI: 10.1111/bjh.17570
|View full text |Cite
|
Sign up to set email alerts
|

Rectus sheath and retroperitoneal haematomas in patients with Coronavirus 2019 infection

Abstract: High rates of venous thromboembolism (VTE) have been observed in Coronavirus 2019 disease . 1 Regulatory bodies in the UK advise pharmacological VTE prophylaxis with standard prophylactic low-molecular-weight heparin (LMWH) dosing, escalating to a therapeutic dose if there is a high clinical suspicion of VTE. 2 Furthermore, in December 2020, an interim analysis of pooled data from the ACTIV-4a, REMAPCAP and ATTACC randomised clinical trials suggested that LMWH was beneficial for patients not requiring intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
2
11
1
2
Order By: Relevance
“…There are concerns over RSH in hospitalized patients with COVID-19 [ 8 13 ]. On the one hand, these patients receive anticoagulants for thromboprophylaxis; on the other hand, any bleeding prompts clinicians to discontinue anticoagulants and control vital signs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns over RSH in hospitalized patients with COVID-19 [ 8 13 ]. On the one hand, these patients receive anticoagulants for thromboprophylaxis; on the other hand, any bleeding prompts clinicians to discontinue anticoagulants and control vital signs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hazenberg et al . noted in a case series 12 patients who had developed either RSH or RPH secondary to enoxaparin injection in COVID-19 positive patients [ 14 ]. Their study identified patients who were predominantly on therapeutic dose enoxaparin and likely developed RPH/RSH due to an extended period of time receiving anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have described retroperitoneal hemorrhage as a fatal bleeding complication ( 19 , 20 ), most of which occurred during anticoagulant therapy in patients with background factors such as older age, hypertension, and combination with aspirin. There are three possible mechanisms for retroperitoneal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%